OPTIMALISASI POTENSI EKONOMI WISATA ALAM DATUK MELALUI INOVASI DISPORABUDPAR DI KECAMATAN SEI SUKA KABUPATEN BATU BARA - Diwayana Putri Nasution; Suhendi Suhendi; Pantun Harianja; Lia Nazliana Nasution; Rusiadi Rusiadi; Bakhtiar Efendi (Jurnal Bina Bangsa Ekonomika, 2024)
This study aims to analyze the improvement of the welfare of the people of Sei Suka District, Batu Bara Regency, through the tourism sector. There are research variables as dependent variables, namely welfare, and there are five independent variables, namely Management, Strategy, Resources, Tourism and Infrastructure. This study used primary data by observing and distributing questionnaires directly to the field. The data analysis model in this study uses SWOT analysis and Multiple Linear Regression method. The partial test results showed that all independent variables had a positive and significant effect on people's welfare. Simultaneously, the results of the study show that Management, Strategy, Resources, Tourism and Infrastructure simultaneously have a significant effect on the welfare of the community in Sei Suka District, Coal Regency